Research progress on simultaneous control of mechanical and magnetic properties of high-strength non-oriented silicon steel for new energy vehicle driving motors - Zhaoyang CHENG; Bolin ZHONG; Zhengxuan NI; Wenqiang JING; Shiqi ZHANG; Jing LIU (工程科学学报, 2023)
New energy vehicles can effectively alleviate the severe dependence of the conventional automobile industry on fossil fuels and the environmental problems worldwide. They are an inevitable requirement in the future development of vehicles. As the power core of new energy vehicles, the driving motors should demonstrate excellent magnetic properties to improve energy conversion efficiency and high strength to resist centrifugal forces during high-speed operation. However, the mechanical and magnetic properties of non-oriented silicon steels remain challenging to balance. Therefore, their coordinated control is a key scientific issue in developing driving motors used in new energy vehicles. This study reviews the regulation of the mechanical and magnetic properties of high-strength non-oriented silicon steels. Additionally, the influence of various strengthening methods on the magnetic properties of non-oriented silicon steels is analyzed. Furthermore, this review highlights the future development of coordinated control of the mechanical and magnetic properties of high-strength non-oriented silicon steels. In non-oriented silicon steels, the dislocation density is relatively low, and the grain size is rather large. Thus, the contribution of dislocation and fine-grain strengthening to the yield strength is minimal. Therefore, by combining fine-grain, dislocation, and solid solution strengthening, the best match in the mechanical and magnetic properties of high-strength nonoriented silicon steels can be obtained. Although the precipitation strengthening effect of alloying elements, such as Nb, Ti, V, and Zr, in nonoriented silicon steels is evident, the carbonitrides formed are coarse-sized and irregularly shaped, which considerably deteriorates the magnetic properties of nonoriented silicon steels. During the early stage of aging treatment, the dispersed Cu precipitates with a BCC structure and fairly small grain size, exhibiting a good strengthening effect. Moreover, these Cu precipitates are coherent with the matrix and exhibit little hindering force on the movement of magnetic domains such that they do not deteriorate the magnetic properties of nonoriented silicon steels. Therefore, employing various strengthening methods or finely dispersed nano-coherent precipitates, nonoriented silicon steels with high strength and excellent magnetic properties can be developed for application in driving motors of new energy vehicles, which is an essential requirement for the high-quality development of the new energy vehicle industry.